Observation of topological surface states and strong electron/hole imbalance in extreme magnetoresistance compound LaBi - Jiang, J.; Schroter, N. B. M.; Wu, S. -C.; Kumar, Nitesh; Shekhar, Chandra; Peng, Han; Xu, X.; Chen, C.; Yang, H. F.; Hwang, C. -C.; Mo, S. -K.; Felser, Claudia; et al. (Physical Review Materials, 2018)
The recent discovery of the extreme magnetoresistance (XMR) in the nonmagnetic rare-earth monopnictides LaX (X = P, As, Sb, Bi,), a recently proposed new topological semimetal family, has inspired intensive research effort in the exploration of the correlation between the XMR and their electronic structures. In this work, using angle-resolved photoemission spectroscopy to investigate the three-dimensional band structure of LaBi, we unraveled its topologically nontrivial nature with the observation of multiple topological surface Dirac fermions, as supported by our ab initio calculations. Furthermore, we observed substantial imbalance between the volume of electron and hole pockets, which rules out the electron-hole compensation as the primary cause of the XMR in LaBi.
CRIS-Team Scopus Importer:2022-04-14